Transactions on Computational Science XIV Special Issue on Voronoi Diagrams and Delaunay Triangulation - Gavrilova, Marina L.; Tan, C. J. Kenneth; Mostafavi, Mir Abolfazl; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The LNCS journal Transactions on Computational Science reflects recent developments in the field of Computational Science, conceiving the field not as a mere ancillary science but rather as an innovative approach supporting many other scientific disciplines. The journal focuses on original high-quality research in the realm of computational science in parallel and distributed environments, encompassing the facilitating theoretical foundations and the applications of large-scale computations and massive data processing. It addresses researchers and practitioners in areas ranging from aerospace to biochemistry, from electronics to geosciences, from mathematics to software architecture, presenting verifiable computational methods, findings, and solutions and enabling industrial users to apply techniques of leading-edge, large-scale, high performance computational methods. The 14th issue of the Transactions on Computational Science journal contains nine papers, all revised and extended versions of papers presented at the International Symposium on Voronoi Diagrams 2010, held in Quebec City, Canada, in June 2010. The topics covered include: the development of new generalized Voronoi diagrams and algorithms including round-trip Voronoi diagrams, maximal zone diagrams, Jensen-Bregman Voronoi diagrams, hyperbolic Voronoi diagrams, and moving network Voronoi diagrams; new algorithms based on Voronoi diagrams for applications in science and engineering, including geosensor networks deployment and optimization and homotopic object reconstruction; and application of Delaunay triangulation for modeling and representation of Cosmic Web and rainfall distribution.
Keywords: Computer science; Data structures (Computer science).; Computer software; Electronic data processing; Computational complexity; Artificial intelligence; Computer graphics; Computer Science; Computer Graphics; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Artificial Intelligence (incl. Robotics).; Data Structures; Numeric Computing